Asthma in athletes and the use of asthma treatment - Balcerek, Tomasz; Lutomski, Przemysław; Grzesiak, Mikołaj (Akademia Wychowania Fizycznego w Poznaniu)
Asthma is a common disease of civilization characterized by a triad of symptoms: coughing, shortness of breath, and wheezing. We know how to diagnose patients with asthma, and the use of provocation tests can accurately determine how big the problem is. Treatment of patients with diagnosed asthma is highly individual. It is based on patient’s education and knowledge of the disease, assessment of the degree of symptoms, possibility of medical treatment and monitoring the patient during the course of drug therapy. The aim of the therapy is to control symptoms associated with asthma. During frequent, intense and prolonged physical exercise at a swimming pool, bronchial shrinking under the influence of the vagus nerve and the hyperventilation of the lower respiratory tract may occur, which are closely related to the changes of humidity and temperature. As a result, a number of irritant effects of chlorine may develop, which can lead to severe asthmatic reactions [2, 4, 7, 9, 10, 12]. This study is a review paper on asthma and exercise-induced asthma in professional swimmers. The first part of the paper is a holistic representation of various aspects of asthma: factors influencing its course, development, diagnosis and therapeutic management. In the second part, the authors discuss the impact of swimming pool water disinfection and hyperventilation on the risk of asthma in swimmers, and to what extent the treatment of asthma in swimmers and professional athletes may count as illegal doping in view of present-day anti-doping regulations
Keywords: asthma; swimming; chlorine